PRESUPPOSITION OF CONFESSIONAL DISCOURSE FUNCTION USED BY THE MAIN CHARACTER IN THE ENOLA HOLMES (2020) - Cisca Fibriana (Language Horizon: Journal of Language Studies, 2024)
This study examines the use of assumptions in confessional language in Enola’s dialogue in the Netflix series Enola Holmes, Season 1, which was released in 2020. The purpose of this study is to determine the types of assumptions that contribute to confessional conversations and how they influence Enola’s character development. This research uses a qualitative approach, with a set of data and documentation. George Yule’s presupposition theory, Mandziuk’s confessional discourse function theory, and Sara Mills’ confessional discourse theory were used to analyze the data. The study investigates what types of presuppositions Enola uses, how the use of presuppositions affects confessional discourse, and how the combination of presuppositions in confessional discourse can build the character’s journey. The study shows that five presuppositions are used: active, existential, lexical, structural, and non-active. The three functions of confessional discourse found were therapeutic, didactic, and interrogatory. The results show that the use of presuppositions in the confessional to create emotions shows disapproval of the standards set by the environment against women.